Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2017)
A dataset containing 2293460 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Buteo jamaicensis (Gmelin, 1788)", "Country is United States of America", { "or" : [ "BasisOfRecord is Human Observation", "BasisOfRecord is Machine Observation", "BasisOfRecord is Observation", "BasisOfRecord is Material sample", "BasisOfRecord is Living Specimen", "BasisOfRecord is Literature Occurrence", "BasisOfRecord is Specimen" ] }, "Year 1997-2017" ] } The dataset includes 2293460 records from 49 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0083927-160910150852091/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences